О влиянии уровня внешнего магнитного поля и длины на магнитный момент цилиндрических сердечников - Чунихин, Константин Вадимович (Національний технічний університет "Харківський політехнічний інститут", 2018)
Рассмотрено магнитостатическое поле неоднородно намагниченного в однородном магнитном поле длинного цилиндрического сердечника электромагнита системы управления космическим аппаратом. Для расчета этого поля предложены преобразование интегрального уравнения относительно плотности фиктивных магнитных зарядов, а так же итерационный алгоритм его численного решения. Сделан анализ влияния длины сердечника из пермаллоя 50Н во всем диапазоне кривой намагничивания и уровня внешнего магнитного поля на осевую проекцию магнитного момента сердечника, а также даны практические рекомендации относительно уровня внешнего поля, создаваемого катушкой электромагнита, и увеличения магнитного момента в случаях длинных сердечников.

Purpose. Analysis of inhomogeneous magnetization of long cylindrical permalloy 50N cores by a uniform constant magnetic field and the influence of length and field level on their magnetic moment. Methodology. The magnetostatic field of a non-uniformly magnetized in a uniform magnetic field long cylindrical core of an electromagnet of a spacecraft control system is considered. To calculate this field, a transformation of the integral equation with respect to the density of fictitious magnetic charges, as well as an iterative algorithm for its numerical solution, are proposed. Results. The convergence of the algorithm and the fact that the magnetic moment of the core depends heavily on its length and the level of the external magnetic field is shown. We have made an analysis of the influence of the length of a permalloy 50N core in the entire range of the magnetization curve and the level of a uniformexternal magnetic field on the axial projection of the magnetic moment of the core. Originality. The use of an almost equal distribution of the axial projection of the resulting magnetic field in the cross sections of the greater part of the cylindrical core and itsdivision into cylindrical elements can significantly reduce the order ofthe system of algebraic equations approximating the integral equation for the surface density of fictitious magnetic charges for its numerical solution. Practical value. Recommendations regarding the level of the external field created by the electromagnet coil, the increase of the magnetic moment in cases of long cores and the choice of the number of cylindrical elements depending on the length of the core are given.
On the influence of the level of an external magnetic field and the length on the magnetic moment of cylindrical cores
Keywords: электромагнит; система управления космическим аппаратом; неоднородно намагниченный сердечник; интегральное уравнение; фиктивный магнитный заряд; кривая намагничивания; electromagnet; spacecraft control system; non-uniformly magnetized core; integral equation; fictitious magnetic charge; magnetization curve